2018
DOI: 10.24198/jt.vol12n1.7
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Energi Pada Proses Pengolahan Teh Hitam Ortodoks (Studi Kasus Pt. Perkebunan Nusantara Viii Kebun Gedeh, Desa Sukamulya, Kecamatan Cugenang, Kabupaten Cianjur, Jawa Barat)

Abstract: Pada proses pengolahan teh membutuhkan energi yang cukup besar sehingga diperlukan suatu analisis sebagai upaya dalam menentukan strategi yang tepat terkait dengan penghematan energi pada rangkaian proses produksi teh hitam. Metode penelitian yang digunakan adalah metode analisis deskriptif menggunakan kuesioner, dimana analisis energi dihitung berdasarkan penggunaan energi pada setiap kegiatan dan menghitung konsumsi energi tenaga manusia dan energi sarana produksi lalu dideskripsikan melalui analisis SWOT. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…For comparison, the processing of orthodox black tea at PT. Perkebunan Nusantara VIII Kebun Gedeh requires biological energy and direct energy of 11,162 MJ/kg in the withering process and in the packing process of 0.321 MJ/kg (Herwanto et al, 2018). It can be concluded that the green tea processing process at The total energy use for green tea processing at the Green Tea Factory PPTK Gambung is 51.141 MJ/kg with an average yield of 14,579 kg/day.…”
Section: Table 2 Total Green Tea Processing Energy At Pptk Gambung Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the processing of orthodox black tea at PT. Perkebunan Nusantara VIII Kebun Gedeh requires biological energy and direct energy of 11,162 MJ/kg in the withering process and in the packing process of 0.321 MJ/kg (Herwanto et al, 2018). It can be concluded that the green tea processing process at The total energy use for green tea processing at the Green Tea Factory PPTK Gambung is 51.141 MJ/kg with an average yield of 14,579 kg/day.…”
Section: Table 2 Total Green Tea Processing Energy At Pptk Gambung Gr...mentioning
confidence: 99%
“…When compared with the results of orthodox black tea processing at PT. Perkebunan Nusantara VIII Kebun Gedeh (Herwanto et al, 2018) which requires a total energy of 73,034 MJ/kg with an average yield of 8,128 kg/day, it can be concluded that with an average yield of 14,579 tons/day of green tea processing in PPTK Gambung could save 21,893 MJ/kg from processing orthodox black tea at PT. Perkebunan Nusantara VIII Kebun Gedeh.…”
Section: Table 2 Total Green Tea Processing Energy At Pptk Gambung Gr...mentioning
confidence: 99%
“…Peningkatan pembangunan di bidang teknologi mempengaruhi penggunaan alat dan mesin yang semakin meningkat khususnya dalam sistem pertanian di Indonesia [1]. Dalam era industri 4.0 saat ini, pemanfaatan teknologi tepat guna untuk meningkatkan produktivitas pertanian di Indonesia sehingga bernilai ekonomis tinggi sangat memungkinkan direalisasikan.…”
Section: Pendahuluanunclassified
“…Proses pengeringan teh merupakan proses yang memakan energi terbesar dari seluruh proses produksi teh, karena bahan bakar terbanyak, terutama bahan bakar padat, seperti kayu bakar, paling banyak digunakan disini [3]. Proses ini menghabiskan sekitar 84,36% energi atau setara 7940 kWh/kg teh yang dikeringkan.…”
Section: Pendahuluanunclassified